Implementation of Total Quality Management at Doloksanggul State Special School in 2023 - Fernan Sinabutar; Oktober Tua Aritonang (Pusat Riset dan Inovasi Nasional, 2023)
Abstract. This study aims to know and describe the implementation of Total Quality Management (TQM) at Doloksanggul State Special School, Humbang Hasundutan Regency, North Sumatra Province. The method used in this study is descriptive-qualitative method. The techniques used in data collection are observation, interviews and documentation studies. Data analysis is carried out by data reduction and data presentation. For data validity tests are carried out by Triangulation. After conducting research at the Doloksanggul State Special School, researchers found several facts that the implementation of Total Quality Management (TQM) at the Doloksanggul State Special School had been implemented properly.